2016
DOI: 10.3389/fpls.2016.01803
|View full text |Cite
|
Sign up to set email alerts
|

ROS Production and Scavenging under Anoxia and Re-Oxygenation in Arabidopsis Cells: A Balance between Redox Signaling and Impairment

Abstract: Plants can frequently experience low oxygen concentrations due to environmental factors such as flooding or waterlogging. It has been reported that both anoxia and the transition from anoxia to re-oxygenation determine a strong imbalance in the cellular redox state involving the production of reactive oxygen species (ROS) and nitric oxide (NO). Plant cell cultures can be a suitable system to study the response to oxygen deprivation stress since a close control of physicochemical parameters is available when us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…The induction of NO after hypoxia in the root occurs rapidly, within minutes, and therefore it has been suggested to be involved in hypoxic stress response in the root 53 . Some of the functions, which have been attributed to hypoxia-induced NO, include a role in the production of ATP 54 , interaction with alternative oxidase (AOX) 55,56 and programmed cell death (PCD) during aerenchyma formation 31,57 . Wany et al (2017) have shown that NO, in addition to ROS, is involved in programmed cell death during ethylene-induced lysigenous aerenchyma formation under hypoxic stress in wheat roots.…”
Section: Hypoxia-induced Ros Production Redox Associated Gene Expresmentioning
confidence: 99%
“…The induction of NO after hypoxia in the root occurs rapidly, within minutes, and therefore it has been suggested to be involved in hypoxic stress response in the root 53 . Some of the functions, which have been attributed to hypoxia-induced NO, include a role in the production of ATP 54 , interaction with alternative oxidase (AOX) 55,56 and programmed cell death (PCD) during aerenchyma formation 31,57 . Wany et al (2017) have shown that NO, in addition to ROS, is involved in programmed cell death during ethylene-induced lysigenous aerenchyma formation under hypoxic stress in wheat roots.…”
Section: Hypoxia-induced Ros Production Redox Associated Gene Expresmentioning
confidence: 99%
“…However, several studies report increased ROS accumulation under hypoxia/anoxia ( Fig. 1; Chang et al, 2012;Pucciariello et al, 2012;Paradiso et al, 2016). Under oxygen deprivation, ROS production likely still occurs in the mitochondria, chloroplasts, and peroxisomes.…”
Section: Ros Metabolismmentioning
confidence: 97%
“…Thus, the same protective mechanisms can act as an integral part of the ERF-VII dependent response strategy to hypoxia. Improved ROS management has been associated with superior submergence tolerance in maize and Brachypodion distachyon (Campbell et al, 2015;Rivera-Contreras et al, 2016), while the activation of antioxidant responses in the posthypoxic phase is crucial for survival in Arabidopsis (Paradiso et al, 2016;Yuan et al, 2017). Interestingly, a target of RAP-type ERF-VIIs, namely HYPOXIA RE-SPONSIVE UNIVERSAL STRESS PROTEIN1, has been shown to coordinate oxygen sensing by PCO/RAP2.12 with H 2 O 2 production by NADPH oxidases, indicating that there is a network connecting diverse signaling pathways downstream of ERF-VII targets (Gonzali et al, 2015).…”
Section: Erf-vii Involvement In Ros-and No-dependent Responsesmentioning
confidence: 99%